Alternative health delivery system through NGO-managed cost-effective regional medical centers - Ponce, Ramon U. (2008)
The common Filipino needing proper medical treatment cannot afford the expensive medical tests, medicines, hospital fees and professional fees which characterize the well-equipped private hospitals concentrated in the national capital region. On the other hand, the government hospitals mostly with limited medical equipment and staffed with underpaid but overworked salaried doctors and nurses can only do so much. The continuing exodus of well-trained and highly skilled medical professionals like doctors and nurses for better compensation in other countries aggravates the problem. Thus, the need to provide accessible quality health care to meet the medical needs of all Filipinos, especially the poor, through an alternative health delivery system characterized by the establishment of NGO-managed cost-effective regional medical centers using public financial support together with comprehensive medical scholarship and continuing career development program.
Keywords: Health services administration; Medical care costs; Health services accessibility; Healthcare facilities; Health care delivery; Health services; Medical care